Incident detection of human papillomavirus – a prospective follow-up study among Tanzanian women with a focus on HIV status - Bariki Mchome; Ditte S Linde; Rachel Manongi; Marianne Waldstroem; Thomas lftner; Chunsen Wu; Julius Mwaisalage; Vibeke Rasch; Susanne K. Kjaer (International Journal of Infectious Diseases, 2021)
ABSTRACT: Background: The causative role of human papillomavirus (HPV) in cervical carcinogenesis is well established; however, prospective studies examining high-risk(HR)-HPV acquisition among adult women in HIV-prevalent settings are limited. Methods: We conducted a prospective study among women (25–60 years) attending cervical cancer screening in Tanzania. Cervical specimens obtained at enrolment and follow-up were tested for HPV. Participants were interviewed on lifestyle and tested for HIV. Results: Among 3805 eligible women, 3074 (80.8%) attended follow-up (median time between the 2 examinations, 17.3 months); 307 had missing HPV results at enrolment or follow-up, leaving 2767 study participants. Among 2253 women initially HR-HPV negative, 184 acquired HR-HPV—incidence: 54.5 per 1000 person-years (95% CI:47.1–62.9); among HIV-positive women 75.2 per 1000 person-years (95% CI:54.5–103.7), HIV-negative 50.9 per 1000 person-years (95% CI:43.3–60.0). HPV52 and HPV16 were the most frequently acquired types. In multivariable regression analysis, HIV positivity, low CD4 count, younger age, and multiple sexual partners were associated with increased odds of HPV acquisition. Conclusion: HPV acquisition was higher among HIV-positive than HIV-negative women, especially women with low CD4 counts. Improvement of immune status among HIV-positives may decrease HPV acquisition. Nonavalent HPV vaccination should be considered given the pattern of HR-HPV types acquired.